Strategi Pemaju Terhadap Pencegahan Dan Pembaikan Kecacatan Bangunan Perumahan - Alias, Muhammad Aiman; Omar, Roshartini; Sarpin, Norliana; Khalid, Zailawati; Shafii, Haryati (Research in Management of Technology and Business, 2023)
Changes in the environment and the way people work can cause damage to buildings. Malaysian construction stakeholders have implemented quantity policies, internal quality training, and quality management systems to reduce housing defects and damage. Changes in the environment, in the way we work, and in the demand and supply of products produced and used by industry and society, in general, can occur due to a number of specific factors. The objective of this study is to identify the main factors that cause frequent damage to completed residential buildings in Malaysia, identify the methods used by developers to prevent and repair defects in newly completed buildings, as well as examine the strategies used by developers to ensure that buildings which is built can be used in the long term. The location of study is located in Selangor because in 2019 the state recorded 2590 maintenance and damage complaints out of 5107 total complaints reported in Malaysia equal to 50.71%. This research focuses on residential developers found in the state. Qualitative methods were used to collect data for this research. The main data collection for the study is through interviews conducted with 3 housing developers in Selangor. The results of the study found that the main factors that cause building defects are connection failure and leakage, incompatibility of building materials, lack of labor experience, cracks, and also unskilled labor. The methods used to reduce defects are the QLASSIC measurement system, BIM, and even UAV aircraft. The building defect strategy is also the result of three (3) subsystems that have been analyzed, namely the technical subsystem, the human resource subsystem, and the management subsystem.